Understanding WiFi-based Connectivity From Moving Vehicles - Mahajan, Ratul; Zahorjan, John; Zill, Brian (Internet Measurement Conference (IMC), 2007)
Using measurements from VanLAN, a modest-size testbed that we have deployed, we analyze the fundamental characteristics ofWiFi-based connectivity between basestations and vehicles in urban settings. Our results uncover a more complex picture than previous work which was conducted in more benign settings. The interval between a vehicle coming into and going out of range of a basestation is often marred by intermittent periods of very poor connectivity. These “gray periods” are hard to reliably predict because their arrival is not signaled by metrics such as signal strength, loss rate, speed or distance from the basestation. At the same time, they also do not consistently occur at the same spot. Our analysis suggests that gray periods are not caused by the motion of the vehicle per se but by the variability in the urban radio environment combined with the vehicle traversing locations that are poorly covered by the basestation. We also find that knowledge of past connectivity can be used to identify regions where gray periods are more likely to occur as well as regions where the vehicle is likely to experience good connectivity.